The EUROpean and Chinese cardiac and renal Remote Ischemic Preconditioning Study (EURO-CRIPS): study design and methods. Issue 3 (March 2015) - Moretti, Claudio; Cavallero, Erika; D'Ascenzo, Fabrizio; Cerrato, Enrico; Zoccai, Giuseppe Biondi; Omedè, Pierluigi; Presutti, Davide Giacomo; Lefevre, Thierry; Sanguineti, Francesca; Picchi, Andrea; Palazzuoli, Alberto; Carini, Giovanni; et al.
Abstract : Aims: Contrast-induced nephropathy (CIN) and periprocedural myocardial infarction (PMI) represent frequent complications of percutaneous coronary intervention (PCI) and negatively impact subsequent length of hospitalization, costs of adjunctive diagnostic–therapeutic measures and mid-term cardiovascular events. The aim of the EURO-CRIPS trial is to test whether remote ischemic preconditioning (RIPC) may reduce the incidence of these complications and improve mid-term outcome. Methods: This will be a double-blind, randomized, placebo-controlled multicentre study. Patients will be allocated 1 : 1 to RIPC or standard therapy if they were younger than 85 years old, with a renal clearance in the interval 30–60 ml/min/1.73 m 2 and candidate to PCI for all clinical indications except for primary PCI in ST segment elevation myocardial infarction (STEMI), unstable haemodynamic presentations or ongoing severe arrhythmias. Incidence of CIN will be the primary end point and the amount of periprocedural cardiac enzyme leakage will be the secondary end point. In addition, we will evaluate whether the preconditioned patients will have a reduction of MACCE at 6 months (major adverse cardiac and cerebrovascular event). Conclusion: The EURO-CRIPS Study will be the first large-scale, multicentre clinical trial to test the role of RIPC in current clinical practice. The results of this randomized trial will provide important insights to optimize management strategy of patients undergoing PCI and to improve their outcome.